Board IT Committees And Firm Performance: A Review Of Literature - Nazahan Qahatan, Rohaida Basiruddin, Raihana Mohdali (International Journal of Advanced Science and Technology, 2020)
The focus of this paper is to provide a review on board IT committees and firm performance. It is believed that at the board level, IT monitoring committee could play an important role in the board functions about governing Information Technology (ITG) and the performance of firms in the medium-sized enterprises apart from the large and listed firms. Unfortunately, only about 10 % of public organisations have established such a committee, thus, creating a knowledge gap. Moreover, past study shows insignificant boards created this type of committee because they lack thorough leadership on the mechanisms and duties of such committees. Efforts are required to close up this gap by designing execution procedures for this form of involvement. The research design covers the aspects of survey research method, cross-sectional analysis, target population, sampling frame, sample size and sampling technique as well as the research instrument of closed-ended questionnaire for the collection of data. Data and empirical analysis are to involve confirmatory factor analysis with path analysis to determine the measurement and structural model via the covariance-based structural equation model. A well-accepted guideline includes the creation of the board level IT monitoring committee, so, an IT monitoring committee need to be created to contribute to the board functions about ITG and its influence on the performance of firms.